Reflections on task-based language teaching - Ellis, Rod (2018)
Task-based language teaching is now a well-established pedagogic approach but problematic issues remain, such as whether it is appropriate for all learners and in all instructional contexts. This book draws on the author’s experience of working with teachers, together with his knowledge of relevant research and theory, to examine the key issues. It proposes flexible ways in which tasks can be designed and implemented in the language classroom to address the problems that teachers often face with task-based language teaching. It will appeal to researchers and teachers who are interested in task-based language teaching and the practical and theoretical issues involved. It will also be of interest to students and researchers working in the areas of applied linguistics, TESOL and second language acquisition.